Disinvestment Policy of India During 2014 to 2020: An Overview: Examining the Disinvestment Policy of India: A Comprehensive Overview (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This article provides a brief overview of the Indian public sector, and discusses changes ingovernment policy toward the public sector. This essay also addresses some disinvestment-relatedquestions, including why, how much, and how to implement disinvestment, as well as its conclusion